EVALUASI PEMBELAJARAN AGAMA ISLAM - Hasanah, Maghfirotul (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This study examines the evaluation of Islamic religious learning to understand the aspects of planning, implementation, assessment results, and final evaluation. This study is a literature study where data is obtained through the stages of orientation, exploration, and concentration on texts or manuscripts in the form of books, papers, and written documents. The results of the study indicate that the evaluation of Islamic religious learning is an assessment technique that not only focuses on the cognitive domain, but also includes the assessment of students' affective and psychomotor domains, such as behavior, manners, and attitudes. The evaluation of Islamic religious learning has specific learning outcomes (CP) and is carried out through several stages to achieve the desired goals. This holistic evaluation allows for a more comprehensive understanding of student development in various aspects, both academic and non-academic, so that it can produce graduates who are not only intellectually intelligent but also have noble character.